Development of a test stand for the evaluation of row crop planter automatic downforce systems and the evaluation of a row crop planter electronic drive singulation seed meter. - Strasser, Ryan Scott (Kansas State University, 2017)
In recent years, the technology employed on precision row-crop planters has rapidly advanced. These new technologies include automatic downforce control systems and electronic drive singulation seed meters. These new technologies offer producers higher productivity through high speed planting and increased yield potentials through accurate seed spacing and placement. To begin to understand the benefits and performance of these new technologies, research must be conducted that specifically targets these new systems. With this research, producers would be able to better select equipment for their operation and have a deeper understanding of proper system operation and settings. A test stand, of a scissor-lift type design, was developed to evaluate row crop planter automatic downforce systems. Evaluation of a planter’s automatic downforce system is important for understanding the planter’s capability of maintaining target seeding depth throughout varying field conditions. The test stand consists of a horizontal platform that can raise and lower to simulate terrain changes as well as a mechanism to load the planter row unit’s opening discs to simulate varying soil texture. The vertical height of the test stand and the disc load can be varied in real-time based on utilizing real-world scenarios under simulated conditions to evaluate downforce system response. The stand incorporated several sensors to obtain the overall applied downforce, applied disc load, applied gauge wheel load, and hydraulic pressure. The test stand’s capabilities were evaluated and found to be satisfactory for planter downforce system testing. The test stand was then used to evaluate a commercial automatic downforce system when operating under simulated field conditions. Field data was used to create simulations representing soil type changes, planter operating speed changes, and extreme conditions such as a hard, packed clay or rocky soil type. It was found that the evaluated downforce system was able to maintain target gauge wheel load to within ±223 N for at least 94% of the time during all simulations. This would suggest that the planter would be able to maintain target seeding depth for at least 94% of field operations. Another key aspect for precision agricultural planters is to achieve accurate seed spacing at varying speeds. An electronic drive singulation seed metering system was evaluated to gather the meter’s effectiveness for high speed planting during straight and contour farming mode using simulated field conditions. The simulated conditions were used to gather the meter’s response when encountering high planting speeds, accelerations, decelerations, point-rows, and contours. These meters were found to be highly accurate, with less than 1.5% error in target seed meter speed during all simulated conditions. The meters were also found to have a response time that was always 0.34 seconds or less for all simulated conditions.
Keywords: Precision agriculture; Downforce; Seed meter